Heterogeneous polymerase fidelity and mismatch repair bias genome variation and composition - Lujan, Scott A.; Clausen, Anders R.; Clark, Alan B.; MacAlpine, Heather K.; MacAlpine, David M.; Malc, Ewa P.; Mieczkowski, Piotr A.; Burkholder, Adam B.; Fargo, David C.; Gordenin, Dmitry A.; Kunkel, Thomas A. (Genome Research, 2014)
Mutational heterogeneity must be taken into account when reconstructing evolutionary histories, calibrating molecular clocks, and predicting links between genes and disease. Selective pressures and various DNA transactions have been invoked to explain the heterogeneous distribution of genetic variation between species, within populations, and in tissue-specific tumors. To examine relationships between such heterogeneity and variations in leading- and lagging-strand replication fidelity and mismatch repair, we accumulated 40,000 spontaneous mutations in eight diploid yeast strains in the absence of selective pressure. We found that replicase error rates vary by fork direction, coding state, nucleosome proximity, and sequence context. Further, error rates and DNA mismatch repair efficiency both vary by mismatch type, responsible polymerase, replication time, and replication origin proximity. Mutation patterns implicate replication infidelity as one driver of variation in somatic and germline evolution, suggest mechanisms of mutual modulation of genome stability and composition, and predict future observations in specific cancers.